1973
DOI: 10.1017/s0021859600058342
|View full text |Cite
|
Sign up to set email alerts
|

Methods of analysing competition with special reference to herbage plants: I. Establishment

Abstract: A diallel arrangement, which incorporated the essential features of the de Wit density replacement series, was employed to study the effects of competition amongst five genotypes of perennial ryegrass (Lolium perenne). Of the five genotypes concerned two were derived from S. 24, two were collected from natural populations in South Wales, while the remaining genotype originated from S. 23. These five genotypes were grown as monocultures and in all ten binary combinations. Within each combination there were thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…Examination of the variances of the data for the sexes showed that the variances were independent. The data for total yield were compared in a replacement diagram (Harper, 1977;Hill and Shimamoto, 1973) and were expressed as relative yield totals (Hall, 1974).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Examination of the variances of the data for the sexes showed that the variances were independent. The data for total yield were compared in a replacement diagram (Harper, 1977;Hill and Shimamoto, 1973) and were expressed as relative yield totals (Hall, 1974).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This variation in the results can be explained by ecological concepts of niche differentiation. Higher productivity of mixtures relative to that of pure stands occurs if the between-species competition is low, and complementarity between species promotes better use of natural resources (Hill and Shimamoto 1973, Snaydon 1991, Möller et al 2008. The yield advantage of binary mixtures over pure stands can be expected when suitable components in the mixture are brought together for specific growing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…From five perennial ryegrass genotypes (clones) used in a previous experiment (Hill and Shimamoto, 1973), three (B, C and E) were chosen for this investigation. Marked morphological differences exist between these three genotypes in that B is short-leaved, densely tillering and with a very prostrate growth habit, whereas both C and E have larger leaves, are less densely tillering and have erect growth habits.…”
Section: The Experimentsmentioning
confidence: 99%